Sodium‐glucose co‐transporter (SGLT)2 and SGLT1 renal expression in patients with type 2 diabetes. Issue 9 (22nd May 2017) - Solini, Anna; Rossi, Chiara; Mazzanti, Chiara M.; Proietti, Agnese; Koepsell, Hermann; Ferrannini, Ele
Abstract : Aim: To quantify the expression of sodium‐glucose co‐transporter (SGLT)2 and SGLT1, their cognate basolateral transporters, GLUT2 and GLUT1, and the transcriptional regulator of SGLTs in renal tissue obtained from people with T2DM and a group of well‐matched people without diabetes. Methods: We measured SGLT2 and SGLT1 expression in unaffected renal tissue from 19 people with T2DM and 20 people without diabetes, matched for age and estimated glomerular filtration rate (controls), undergoing unilateral nephrectomy. Expression of SGLT2 and SGLT1, as well as that of GLUT2 and GLUT1, was quantified using real‐time and digital PCR; an affinity‐purified antibody against human SGLT2 was used to localize SGLT2 by immunohistochemistry. Results: SGLT2 expression was higher in control than T2DM tissue (median [interquartile range] target/β‐actin 1.62 [2.02] vs 0.67 [0.61]; P  < .0001), and SGLT1 trended in the same direction (0.98 [1.19] vs 0.44 [0.48]; P  = .08). Immunohistochemistry clearly localized SGLT2 to the tubular brush‐border membranes, and was semi‐quantitatively stronger in control than T2DM tissue (5.0 [1.0] vs 4.0 [1.0] score units; P  = .043). GLUT2 (control vs T2DM: 1.00 [0.69] vs 0.49 [0.36]) and GLUT1 expression (control vs T2DM: 0.86 [0.73] vs 0.35 [0.30]; P  = .0007 for both) were closely correlated with those of the respective SGLT partner. Hypoxia‐inducible factor 1α, more abundant in control than T2DM tissue, might be a transcription factor involved in the modulation of SGLT2 expression. Conclusions: In whole renal tissue, expressions of SGLT2/GLUT2 and SGLT1/GLUT1 are coupled and slightly lower in typical people with T2DM as compared with well‐matched people without diabetes.